Information literacy in the digital age: information sources, evaluation strategies, and perceived teaching competences of pre-service teachers - Trixa, Jessica; Kaspar, Kai (Frontiers in Psychology, 2024)
Introduction Information literacy has become indispensable in navigating today’s fast-paced media environment, with teachers playing a pivotal role in fostering reflective and critical digital citizenship. Positioned as future gatekeepers, pre-service teachers are the key to teaching media skills and especially information literacy to future generations of pupils. Given the particular challenges facing educators today compared to previous generations, it is important to determine whether the next generation of teachers feel adequately prepared and perceive themselves as competent to pass on these skills to their future pupils. However, previous research has highlighted deficiencies in formal learning opportunities at universities, underscoring the need for further investigation into pre-service teachers’ information acquisition, evaluation practices as well as their perceived relevance to teaching, and person-related factors associated with their perceived competence in teaching information literacy. Method An online questionnaire was presented to participants, employing a mixed-method approach. We qualitatively examined the sources of information used by pre-service teachers and the evaluation strategies they employ, while quantitatively analyzing relationships between pre-service teachers’ person-related factors and their perceived teaching competence. Participants assessed their perceived teaching competence, perceived learning opportunities, self-efficacy (general and related to information assessment), perceived informedness, selective exposure, need for cognition, need for cognitive closure, and mistrust in media coverage. Results Data from 371 participants revealed digital media dominance in information acquisition over traditional sources, albeit with a prevalence of surface-level evaluation strategies over reflective approaches. Two distinct dimensions of perceived competence in teaching information literacy emerged: one focusing on information assessment while the other centers on the understanding of news creation processes. Perceived competence in teaching information literacy was significantly associated with self-efficacy in information assessment, perceived informedness, selective exposure to information as well as perceived learning opportunities focusing on information evaluation. Moreover, pre-service teachers employing diverse information evaluation strategies demonstrated a heightened sense of perceived competence in teaching information assessment. Discussion Our results provide valuable insights into the multifaceted nature of pre-service teachers’ perceived competence in teaching information literacy. Theoretical implications for future research as well as practical implications for teacher education and the structure of future curricula are discussed.